1972
DOI: 10.1037/h0033145
|View full text |Cite
|
Sign up to set email alerts
|

Ersatz egocentrism: A reply to H. Borke.

Abstract: This study, prompted by an earlier and seemingly contradictory report by Borke, presents information which sharply differentiates between role or perspective taking skills and the more primitive and developmentally prior ability to sometimes correctly anticipate the thoughts and feelings of others. In contrast to the data of Borke, which attributed perspective taking skills to children as young as 3 years of age, the present findings, based on the responses of 86 children between the ages of 6 and 12, suggest … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
68
0
3

Year Published

1981
1981
2016
2016

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 129 publications
(73 citation statements)
references
References 3 publications
2
68
0
3
Order By: Relevance
“…The items are based on neoteny, child cognition, and more generally psychology literature, and they cover the following six neoteny-related characteristics: play (P. G. Bateson, 1976;Bekoff, 1972;Bjorklund, 1997;Bjorklund & Pellegrini, 2000;Dansky, 1980;Fagen, 1981;Klinger, 1969;Lorenz, 1971;Pellegrini & Bjorklund, 2004;Pellegrini & Smith, 1998;Piaget, 1945Piaget, /1999Vygotsky, 1930Vygotsky, /2004Vygotsky, , 1931Vygotsky, /1991Vygotsky, , 1933Vygotsky, /1967, attachment (Bowlby, 1969(Bowlby, /1982Cairns, 1976;Fraley, Brumbaugh, & Marks, 2005;Fraley & Shaver, 2000;Hazan & Shaver, 1987Insel, 2000), regression (Fischer, 1987;Lindahl, Heimann, & Ullstadius, 2003;Plooij & van de Rijt-Plooij, 1989;van de Rijt-Plooij & Plooij, 1992), egocentrism (Arnett, 1992;Arnett & BalleJensen, 1993;Bjorklund, Gaultney, & Green, 1993;Buss, 1997;Chandler & Greenspan, 1972;Elkind, 1967Elkind, , 1978Gnepp, 1983;Greene, Krcmar, Walters, Rubin, & Hale, 2000;Harter & Pike, 1984;Looft, 1972;…”
Section: Materials and Proceduresmentioning
confidence: 99%
“…The items are based on neoteny, child cognition, and more generally psychology literature, and they cover the following six neoteny-related characteristics: play (P. G. Bateson, 1976;Bekoff, 1972;Bjorklund, 1997;Bjorklund & Pellegrini, 2000;Dansky, 1980;Fagen, 1981;Klinger, 1969;Lorenz, 1971;Pellegrini & Bjorklund, 2004;Pellegrini & Smith, 1998;Piaget, 1945Piaget, /1999Vygotsky, 1930Vygotsky, /2004Vygotsky, , 1931Vygotsky, /1991Vygotsky, , 1933Vygotsky, /1967, attachment (Bowlby, 1969(Bowlby, /1982Cairns, 1976;Fraley, Brumbaugh, & Marks, 2005;Fraley & Shaver, 2000;Hazan & Shaver, 1987Insel, 2000), regression (Fischer, 1987;Lindahl, Heimann, & Ullstadius, 2003;Plooij & van de Rijt-Plooij, 1989;van de Rijt-Plooij & Plooij, 1992), egocentrism (Arnett, 1992;Arnett & BalleJensen, 1993;Bjorklund, Gaultney, & Green, 1993;Buss, 1997;Chandler & Greenspan, 1972;Elkind, 1967Elkind, , 1978Gnepp, 1983;Greene, Krcmar, Walters, Rubin, & Hale, 2000;Harter & Pike, 1984;Looft, 1972;…”
Section: Materials and Proceduresmentioning
confidence: 99%
“…Social cognitive theory (Selman & Byrne, 1974;Fiavell, 1968) and research (Chandler & Greenspan, 1972;Greenspan, Barehboim & Chandler, 1976) offer some evidence for hypothesizing that social role-taking skill might improve considerably between first and third grade. Therefore, there is reason to believe the ability to apply cognitive and affective role-taking skills when observing aggressive interactions will improve between these ages.…”
Section: Statement Of Problemmentioning
confidence: 99%
“…Children between the ages of four-and-a-half and five-and-a-half years of age respectively, gave the correct response to "sad" and indicated the results demonstrated that very young children were capable of anticipating another person's feelings. Chandler and Greenspan (1972) criticized Borke's (1971) results as reflecting a stereotype based on projection, instead of insight as a function of role-taking. In an attempt to differentiate between a more primitive ability to sometimes correctly anticipate the thoughts and feelings of others, and a role-taking skill based on decentration.…”
mentioning
confidence: 99%
See 2 more Smart Citations